Patient Non-Adherence to Medication in Inflammatory Bowel Disease - Alan BR Thomson (Canadian Journal of Gastroenterology)
Dr Sewitch and colleagues at the University of Montreal and McGill University undertook a prospective study that provided evidence for the important relationship between patient-physician discordance and patient nonadherence with medication for inflammatory bowel disease (IBD).